Metode latihan drill bowling Terhadap ketepatan bowler - Firmansyah, Dhimas Ariij; Supriatna, Mr (Indonesian Journal of Sport and Physical Education, 2020)
Abstract: This study aims to determined the effect of the method of bowling drill training on the accuracy of the bowler. This study used a pre-experimental research design with the design of one group pretest posttest design. The subjects used were six male athletes' bowlers selected from the Malang State University cricket team aged 18 to 21 years. This study was conducted for 18 meetings with a frequency of exercise 3 times a week in 6 weeks. The research test instrument used the Amir Majeed Bhat Bowling Skill Test. The results of the average pretest are 21.16 and for the results of the posttest average is 30.50. Data obtained from the results of the pretest and posttest were analyzed using analyze paired samples t-test. The results of the paired t-test analysis were 0,000 <0,05. If the results of the analysis are smaller than the significance level, it can be concluded that there is a significant effect on the method of bowling drill training on the accuracy of the bowler. Keywords: Bowler, Method of Bowling Drill Training, Bowling, Accuracy Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh metode latihan drill bowling terhadap ketepatan bowler. Penelitian ini menggunakan rancangan penelitan pre-experimental dengan desain one group pretest posttest design. Subjek yang digunakan sebanyak enam bowler atlet putra dipilih dari tim cricket Universitas Negeri Malang berusia 18 hingga 21 tahun. Penelitian ini dilakukan selama 18 kali pertemuan dengan frekuensi latihan 3 kali seminggu dalam 6 minggu. Instrumen tes penelitian ini menggunakan Amir Majeed Bhat Bowling Skill Test. Hasil dari rata-rata pretest adalah 21,16 dan untuk hasil dari rata-rata posttest adalah 30,50. Data yang diperoleh dari hasil pretest dan posttest dianalisis menggunakan analyze paired samples t-test. Hasil dari analisis paired t-test adalah 0,000 < 0,05. Jika hasil analisis tersebut lebih kecil dari taraf signifikansi, maka dapat disimpulkan bahwa ada pengaruh yang signifikan metode latihan drill bowling terhadap ketepatan bowler. Kata kunci: Bowler, Metode Latihan Drill, Bowling, Ketepatan